Pembelajaran integratif dalam pendidikan bahasa Indonesia: sebuah tinjauan literatur sistematis - Laili, Talitha Sahda; Mulyati, Yeti (Universitas Mulawarman, 2024)
In the era of industrial revolution, education is required to produce graduates who are in line with 21st century skills. One of the learning models that is considered suitable for the challenges of this century is integrative learning. Specifically, this research explores the concept of interdisciplinary integrative learning in Indonesian language learning, starting from the principles, steps, to the impact of learning for students. This research used the SLR (systematic literature review) method. Data was obtained through the Publish or Perish application. From 224 articles found, 5 articles were selected that were in line with this research. Based on the search results, it was found that the principles of learning with the integrative learning model are (1) student-centered learning; (2) integrating various disciplines; and (3) utilizing technology. The implementation of integrative learning in Indonesian language learning can be done by combining various learning methods or various disciplines in learning. Through this model, Indonesian language learning at school becomes more meaningful because students are able to master linguistic insights and can use them in everyday life. In addition, this model also helps students to understand knowledge holistically to solve problems in everyday life.